Assessment of antibiotic residues in beef cattle slaughtered in Bangladesh: Implications for food safety and public health - Kamal, MT; Deen, RA; Ahmed, B; Hashem, MA (Meat Research, 2025)
This study investigates the concentrations of tetracycline, ciprofloxacin, and enrofloxacin residues in various tissues of beef cattle post-slaughter in Bangladesh, emphasizing their implications for food safety and public health. Residue levels were analyzed across heart, kidney, liver, lung, and muscle tissues, utilizing high-sensitivity detection methods. The findings reveal that Tetracycline is present in all tested tissues, with the highest concentration observed in heart tissue (109.68 ppb) and the lowest in the liver (55.19 ppb), all remaining below the international maximum residue limits (MRLs). Ciprofloxacin was detected primarily in kidney and liver tissues, with concentrations substantially below the detection limits in heart, lung, and muscle. Enrofloxacin showed the highest residue levels in muscle tissues (45.36 ppb) and was undetectable in kidney and liver. These results highlight effective antibiotic residue management in the evaluated tissues, with all concentrations safely below MRLs, ensuring compliance with global food safety standards. However, the observed presence of these antibiotics, particularly the variations in residue levels, underscores the need for stringent monitoring and regulation to prevent potential health risks associated with antibiotic resistance and hypersensitivity reactions. This study contributes to the ongoing efforts to safeguard public health by providing a comprehensive evaluation of antibiotic residues in beef, thereby reinforcing the importance of adherence to pharmacological guidelines and regulatory standards in livestock management.